2015
DOI: 10.1111/jbi.12610
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary history of the subnival flora of the Himalaya‐Hengduan Mountains: first insights from comparative phylogeography of four perennial herbs

Abstract: Aim The Himalaya-Hengduan Mountain (HHM) biodiversity hotspot including the 'sky islands' of Southwest China harbour exceptional plant diversity and endemicity at subnival summits (most of them exceeding 4300 m a.s.l.). This study is the first using a comparative phylogeographical framework to gain insights into the temporal origin of this highly fragmented subnival flora, and the historical factors shaping its genetic architecture as exemplified by four perennial herbs.Location Himalaya-Hengduan Mountains, Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
70
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(74 citation statements)
references
References 61 publications
2
70
2
Order By: Relevance
“…When combined with the general lack of IBD, The island-like population genetic structure of three oak species in accordance with their highly fragmented habitats located in the EH-HM region, and largely driven by historical effects of genetic drift rather than currently limited gene flow alone (Hutchison and Templeton, 1999). In fact, similar genetic structure have also been detected in other species in this region, such as Garrulax elliotii from the eastern Himalayas (Qu et al, 2011) and four herbs from HHM region (Luo et al, 2015). …”
Section: Discussionsupporting
confidence: 61%
“…When combined with the general lack of IBD, The island-like population genetic structure of three oak species in accordance with their highly fragmented habitats located in the EH-HM region, and largely driven by historical effects of genetic drift rather than currently limited gene flow alone (Hutchison and Templeton, 1999). In fact, similar genetic structure have also been detected in other species in this region, such as Garrulax elliotii from the eastern Himalayas (Qu et al, 2011) and four herbs from HHM region (Luo et al, 2015). …”
Section: Discussionsupporting
confidence: 61%
“…Moreover, the high level of total genetic diversity and low levels of within‐population diversity are typical for high mountainous plants, especially in island‐like populations (Luo et al . ). Previous studies have shown that species restricted to sky islands commonly have high levels of interpopulation genetic divergence (Shepard & Burbrink ), consistent with the significant differentiation between these oak populations.…”
Section: Discussionmentioning
confidence: 97%
“…On the other hand, Chionocharis hookeri (C.B.Clarke) I.M.Johnst. is a highly distinctive species of high alpine cushion-forming plants (3500-5800 m) distributed from northeast India to China (Zhu & al., 1995;Luo & al., 2016). Johnston (1924) suggested a close relationship with the Himalayan Lasiocaryum I.M.Johnst.…”
Section: Version Of Recordmentioning
confidence: 99%